Jejaring Advokasi Kebijakan dalam Mendukung Gerakan Anti Korupsi di Daerah Studi Tentang Aktor dan Strategi Kelompok - Hery Firmansyah (Magister Administrasi Publik, 2010)
This article examines the effectiveness of networking advocacy system in the eradication of corruption in the local government. The principal argument is that various approaches to combat corruption have not been effective which implies the need for different alternatives. The study intends to determine the role of actors involved in building system advocacy network in supporting anti-corruption movement in local governments, particularly in cases of corruption that involved school textbooks in Slean district. The result of this study indicate that the networking system of advocacy for the eradication of corruption in the region, involving people in power (regent) in this case study is not effective. This can be judged from the handling of the legal process which still very slow. To that end, there is need to take advantage of networking advocacy system to enhance synergy among acors in anti-corruption (public, university student/ university/ NGO’s media) in controlling corruption cases. The main problem in building advocacy networks among actors is the diversity of agenda of different actors as well as lake of consistency and little knowledge in building the networking movement. This study recommends that anti-corruption actors in local government should play a role in “capacity building from within” with the institutions directly related to anti-corruption agenda. More ever, there is also need for “pressure form without” achieved through strengthening of the anti-corruption agenda.